Development Implications of Ceded Lands by the Cameroon Development Corporation on Fako Division- South West Region of Cameroon from 1960 to 2010 - Eno, Cynthia O.; Fombe, Lawrence F. (Advances in Social Sciences Research Journal, 2016)
The availability of Surrendered lands has enormously facilitated the process of transformation and development of Fako Division in the South West Region of Cameroon from a predominantly underdeveloped rural and agricultural oriented society in the latter half of the 20th Century to a developed urban society. This is visible in terms of expansion in the quantity and quality of residential neighborhoods, health and educational establishments. The significant contribution of surrendered land to the urbanisation process of Fako has once again secured an important place for land in planning and development discourse of the division in particular and Cameroon in general. Using the traditional social science methodology, primary data was collected from the Cameroon Development Corporation (CDC). The data was analysed and presented using a map, table and pie charts. Findings suggest that the expansion and growth in neighborhoods accompanied by a transformation from congested, squalid neighborhoods of substandard housing is an outcome of the availability of new territory surrendered by the large scale plantation company (CDC) to the population for modern investment structures. The transformation in housing has improved health care standard. Such housing development zones have enhanced educational and health standards, through the creation of numerous hospital and schools which have had a combined positive developmental effects on the division. However, to ensure sustainability in surrendered lands, a holistic planning approach must be factored into the developmental strategies of Fake to enhance the efforts of the traditional authorities before, during and after the process of land cessation. KEY WORD: Development Implications, Surrendered Lands, Land Use, Fako Division, CDC.